Computation of Spectral Parameter of Discontinuous Dirac Systems with a Gaussian Multiplier - Mohammed M. Tharwat; Mohammed A. Alghamdi (Abstract and Applied Analysis)
We aim in this paper to apply a sinc-Gaussian technique to compute the eigenvalues of a Dirac system which has a discontinuity at one point and contains a spectral parameter in all boundary conditions. We establish the needed properties of eigenvalues of our problem. The error of this method decays exponentially in terms of the number of involved samples. Therefore the accuracy of the new technique is higher than the classical sinc-method. Numerical worked examples with tables and illustrative figures are given at the end of the paper.